Simulation of finished and thermal stocks of two-stroke engine piston modified with catalytic material - P. V. Litvinov; V. A. Borisov; V. R. Vedruchenko; Z. N. Gryaznova; I. V. Kotsyba (Омский научный вестник)
The calculations of the thermal and stress-strain state of the two-stroke gasoline engine (CS5200) pistons are completed. The model of an original piston and a piston modified with catalytic materials is used in the calculations. The technique used in modeling static and thermal loads using the SolidWorks Simulation program is described. A comparative analysis of the results of modeling the original and modified pistons is given. The efficiency of the piston is estimated when the surface is modified with catalytic materials. The technique for estimating the boundary conditions is used to solve thermal and mechanical problems. It allows you to take into account the features of loading, as well as the available calculated and experimental data.